Labour market transitions in Italy Job separation, re-employment and policy implications - Jin, Yosuke (OECD Economics Department Working Papers, 2016)
Italy's low employment rate is associated with adverse labour market dynamics characterised differently across different categories of people. Both job separation and re-employment have remained less frequent in Italy, especially among older workers, against the backdrop of rigid employment protection legislation which weighs down job creation, thus re-employment prospects. Working conditions after re-employment tend to worsen, especially for older workers, as seniority is not entirely portable across firms. Prospects on working conditions after re-employment deteriorate with longer unemployment spells, affecting incentives to return to work, especially where social benefits are too generous. Rigid employment protection for incumbent workers has also come at the cost of more frequent labour turnover for temporary workers who face an increasing risk of unemployment, including the more highly educated. The risk of hysteresis effects is significant in particular for those who separated from temporary jobs. The public employment service has to take account of individual cases, adopting intensive programmes such as training where necessary, while in general personalised job search assistance to get jobseekers back to work at early stages is recommended